2015
DOI: 10.5897/jmpr2014.5693
|View full text |Cite
|
Sign up to set email alerts
|

Lectin isolated from Brazilian seeds of velvet bean (Mucuna pruriens (L) DC.) presents analgesic, anti-inflammatory and antihemolytic action

Abstract: Lectins are proteins present in all living beings capable of interacting specifically and reversibly to carbohydrates or glycoconjugates form. They stand out in this family of lectins legumes, which are of special scientific interest because they have different biological functions. This study investigated the presence of a lectin in Brazilian seeds of Mucuna, proceeding with their isolation and evaluation of its antinociceptive effects, anti-inflammatory and antihemolytic activity. Saline extracts of Mucuna p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Several studies have shown that L-3,4-dihydroxyphenylalanine (L-DOPA), lectin, isoflavanones, and some alkaloids contained in M. pruriens seeds are responsible for the enormous bioactivity of its crude extracts [9,10]. Recently, several therapeutic approaches have been adopted to make healthy living affordable to all regardless of their status in the society, since synthetic products are not only expensive but also come with adverse effects [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that L-3,4-dihydroxyphenylalanine (L-DOPA), lectin, isoflavanones, and some alkaloids contained in M. pruriens seeds are responsible for the enormous bioactivity of its crude extracts [9,10]. Recently, several therapeutic approaches have been adopted to make healthy living affordable to all regardless of their status in the society, since synthetic products are not only expensive but also come with adverse effects [11,12].…”
Section: Introductionmentioning
confidence: 99%
“… Sapindaceae Seed [80] Glucose/mannose HSV-1 [81] Mangifera indica L. Anacardiaceae Fruit seed [82] Non-specified HSV, influenza virus [83] , [84] Momordica charantia L Cucurbitaceae Seed [85] Galactose/ N-Acetylgalactosamine HIV, HSV-1, H1N1, H3N2, H5N1 [86] , [87] , [88] Mucuna pruriens (L.) DC. Fabaceae Seed [89] Mannose HCV [90] Musa paradisiaca L. Musaceae Ripe fruit pulp [91] Mannose HSV-1, HSV-2 [91] Oryza sativa L. Poaceae [82] N-Acetylglucosamine CMV, HSV [92] , [93] Phaseolus vulgaris L. Fabaceae Seed [94] , [95] Galactose HIV-1 RT [94] , [95] Psidium guajava L. Myrtaceae Fruit [96] Galactose H1N1 [97] Pisum sativum L. Fabaceae Seed [82] , [98] Mannose/galatose HCV, ADV [98] , …”
Section: Introductionmentioning
confidence: 99%